2016
DOI: 10.1016/j.ssi.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Ni/YSZ electrodes structures optimized for increased electrolysis performance and durability

Abstract: Cermet Ni/YSZ electrodes are the most commonly applied fuel electrode for solid oxide cells (SOC) both when targeting solid oxide fuel cell (SOFC) applications and when used as solid oxide electrolysis cell (SOEC). In this work we report on the correlation between initial Ni/YSZ microstructure and the resulting electrochemical performance both initially and during long-term electrolysis testing at high current density and high p(H2O) inlet. Especially, this work focuses on microstructure optimization to hinder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
183
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 198 publications
(209 citation statements)
references
References 37 publications
14
183
2
1
Order By: Relevance
“…Evidently cell C is the better performing. Analysis of impedance spectra recorded at these electrolysis test conditions at start of the test reveals that the polarization resistance attributed to the electrochemical reactions in the Ni/YSZ electrodes were 98 mcm 2 and 38 mcm 2 for cell A and C, respectively (8). Both cells experience an initial increase in Rp; for both cells Rp subsequently reaches a constant level.…”
Section: Ni/ysz Fuel Electrodesmentioning
confidence: 97%
See 1 more Smart Citation
“…Evidently cell C is the better performing. Analysis of impedance spectra recorded at these electrolysis test conditions at start of the test reveals that the polarization resistance attributed to the electrochemical reactions in the Ni/YSZ electrodes were 98 mcm 2 and 38 mcm 2 for cell A and C, respectively (8). Both cells experience an initial increase in Rp; for both cells Rp subsequently reaches a constant level.…”
Section: Ni/ysz Fuel Electrodesmentioning
confidence: 97%
“…Several parameters (e.g. Ni/YSZ ratios, layer thicknesses, particle sizes and sintering temperature) have been investigated to optimize the production of the 4-layer co-sintered half-cells (8,40,41). In recent years processing optimization has also focused on the shift towards -if not completely water based slurries then at least -environmentally friendly production as reported by Foghmoes and co-workers (42).…”
Section: Processing and Microstructuresmentioning
confidence: 99%
“…Predominant fuel electrode degradation was concluded from the electrochemical analysis, which is thus confirmed by the percolation images taken from hydrogen outlet in Figure 10. A loss of active TPBs seems thus responsible for the observed degradation (13,23,28). A gap in the layers is observed in the outlet, at the interface of CGO and YSZ layers (see marker on Figure 10(b)).…”
Section: Microstructural Analysismentioning
confidence: 93%
“…Degradation is observed at the fuel electrode for both high frequency process (1-10 kHz) and medium frequency process (100-1000 Hz). Previous studies have indicated the loss in percolation of Ni network to be one of the major causes for the Ni-YSZ active electrode degradation (12)(13)(14)28). This phenomenon will be investigated in the microstructural analysis.…”
Section: Processmentioning
confidence: 98%
See 1 more Smart Citation